Respiratory muscle training positively affects vasomotor response in young healthy women. - Angela Valentina Bisconti (PLoS ONE, 2018)
Vasomotor response is related to the capacity of the vessel to maintain vascular tone within a narrow range. Two main control mechanisms are involved: the autonomic control of the sympathetic neural drive (global control) and the endothelial smooth cells capacity to respond to mechanical stress by releasing vasoactive factors (peripheral control). The aim of this study was to evaluate the effects of respiratory muscle training (RMT) on vasomotor response, assessed by flow-mediated dilation (FMD) and heart rate variability, in young healthy females. The hypothesis was that RMT could enhance the balance between sympathetic and parasympathetic neural drive and reduce vessel shear stress. Thus, twenty-four women were randomly assigned to either RMT or SHAM group. Maximal inspiratory mouth pressure and maximum voluntary ventilation were utilized to assess the effectiveness of the RMT program, which consisted of three sessions of isocapnic hyperventilation/ week for eight weeks, (twenty-four training sessions). Heart rate variability assessed autonomic balance, a global factor regulating the vasomotor response. Endothelial function was determined by measuring brachial artery vasodilation normalized by shear rate (%FMD/SR). After RMT, but not SHAM, maximal inspiratory mouth pressure and maximum voluntary ventilation increased significantly (+31% and +16%, respectively). Changes in heart rate variability were negligible in both groups. Only RMT exhibited a significant increase in %FMD/SR (+45%; p<0.05). These data suggest a positive effect of RMT on vasomotor response that may be due to a reduction in arterial shear stress, and not through modulation of sympatho-vagal balance.